Captivating Combustion Traits of Bio-Oil Droplets Enriched with Bio-Additives from the Areca Shell Waste - Raehan, Muhammad Alif; Riupassa, Helen; Nanlohy, Hendry Yoshua (Universitas Negeri Malang, 2024)
Fuel derived from crude vegetable oil, such as coconut oil, holds promise as an alternative energy source to mitigate the increasing reliance on fossil fuels driven by population growth and industrial activities. The experiment involved suspending a single droplet of crude coconut oil mixed with activated carbon from areca shell waste and placed at the junction on R-type thermocouple (Pt/Pt-Rh13%). The droplets were ignited using a hot wire and subjected to atmospheric pressure and room temperature. Coconut oil comprises a saturated triglyceride carbon chain compound of approximately 91%, and areca shell waste possesses a porous structure that fosters favorable interactions between fuel molecules. The droplet combustion method was selected to streamline the process and enhance the contact area between air and fuel, thereby boosting the reactivity of fuel molecules. The research found that adding activated carbon shortens the carbon chain, making it more reactive and easier for the fuel to ignite. Specifically, activated carbon significantly enhances fuel performance at a concentration of two parts per million (ppm). At this level, the fuel absorbs heat more effectively and ignites faster compared to one ppm and three ppm levels. Moreover, the results show that heat absorption occurs slowly at one ppm, while at three ppm, the increased molecular mass of the fuel can strengthen carbon-bonding forces. These factors contribute to a longer ignition time for the fuel. The findings suggest that the activated carbon from areca shell waste can play a good role as a combustion catalyst, where overall, fuel performance increases.